The effect of prosthetic alignment on lower limb kinetics in people with a transtibial bone-anchored prosthesis: An experimental within-subject study - Groeneveld, Alyssa M.G.; Jonkergouw, Niels; Bruijn, Sjoerd M.; Houdijk, Han; Kooiman, Vera G.M.; Leijendekkers, Ruud A.; Prins, Maarten R. (Gait & posture, 2025)
The alignment of a bone-anchored prosthesis has consequences for the external moments around the residual joints and implant, and these external moments can lead to serious negative long-term effects. A clear understanding of the relationship between transtibial prosthetic alignment and external joint and implant moment for bone-anchored prosthetic users is still lacking. What is the effect of systematic frontal plane prosthetic alignment changes on lower limb external joint moments in people with a transtibial bone-anchored prosthesis? Participants underwent gait analysis on an instrumented dual belt treadmill. Between analyses, frontal-plane alignment adjustments were made, shifting the prosthetic foot 2, 4, and 6 mm medial and lateral in relation to the residual limb. The effect of alignment changes on frontal- and sagittal plane external joint moments during the stance phase of gait were assessed at the hip, knee, and implant level, using statistical parametric mapping regression analyses. Twenty-seven unilateral transtibial bone-anchored prosthesis users were included. Alignment changes had a significant effect on external frontal plane knee and implant moments on the prosthetic side, with the largest effect at the level of the implant. Incremental medial and lateral displacements resulted in a progressive increase or decrease of the external adduction moments, respectively. Alignment changes did not significantly affect external moments around the prosthetic hip, non-prosthetic joints in the frontal plane or in any of the evaluated joints or implant in the sagittal plane. Mediolateral foot alignment changes have a considerable effect on the frontal plane external knee and implant moments at the prosthetic side of a transtibial bone-anchored prosthesis. The findings of this study can help prosthetists to anticipate and adjust alignment changes for transtibial BAP users to minimize joint moments before issues arise. •Effects of frontal plane prosthetic alignment changes on gait kinetics were assessed.•Implant and knee joint moments were affected by small alignment changes.•Medial shifts increase external adduction moments at the knee and implant.•Alignment changes did not affect non-prosthetic limb moments.•Findings show the importance of alignment in relation to ipsilateral joint health.